Dry Sliding Investigation Of An Activated Carbon-Epoxy Composite Extracted From Palm Kernel - Mahmud, Dayang Nor Fatin (2020)
Nowadays, a lot of alternative technologics have been introduced for the sustainability of global need to save energy by reducing friction and wear of components or parts. Globally, Malaysia is one of the largest consumers and exporters of palm oil. The palm oil generates a large quantity of waste consisting of around 90% of biomass waste and only around 10% of the palm oil. The use of agricultural waste as new composite material has also been found to be renewable and relatively less expensive and ultimately could utilize the waste effectively into wealth. Therefore, this motivate to investigate the potential of activated carbon derived from one of the largest waste palm oils called palm kernel to be new tribological material such as thin film coating, green lubricants and bio/eco- materials. There were few research studies that mentioned the effects of operating conditions on tribological characteristics of an activated carbon-epoxy composite derived from palm Kernel, such as applied load, temperature and sliding distance. However, studies on the Simultaneous effects of contact pressure and sliding speed are limited. Thus, the objective of this work is o investigate the influence of contact pressure and sliding speed on the coefficient of friction and the wear of an activated carbon-epoxy composite derived from palm kernel under dry sliding conditions. A disc sample with diameter of 74 mm with height 5mm was produced by using the hot compaction technique. When the disc samples Were completed, the physical-material test were done. Later, in this study the dry sliding test was executed utilising a ball-on-disc tribometer by applying various contact pressures from 59.84 Pa to 119.99 Pa and sliding speeds from 200 rpm to 500 rpm with a constant Sliding distance at 3000 m and operating temperature at 27°C. This tribological test was conducted according to ASTM 52100 chrome steel ball. The results found that regardless of sliding speed, the friction coefficient and wear rate of the composite increased drastically when exceeding a critical limit of contact pressure. The mechanism of frictional Stability of activated carbon derived from palm kernel composite was analysed by phase transformation study. In addition, phase transformation of the activated carbon composite derived from palm kernel changed from a carbon-like-structure to a graphite-like-structure (5p2) in the top layer of the composites. A wear mode map approach Was employed to identify the transitions from mild to severe wear of the composite. Conclusively, activated carbon derived from palm kemel epoxy disc composite has high potential as the self- Jubricating material.